Analisis Penggunaan Modal Kerja dalam Meningkatkan Laba PT Handjaya Mandala Sampoerna Tbk di BEI - Riska Riska; Emma Lilianti; Rismansyah Rismansyah (Jurnal Media Akuntansi (Mediasi), 2019)
ABSTRACT This study aims to determine how the analysis of the use of working capital in increasing profit at PT. Handjaya Mandala Sampoerna Tbk, which is listed on the Indonesia Stock Exchange. The analytical method used is descriptive and comparative analysis method using working capital adequacy ratio which consists of three ratios, namely the ratio of total assets to current ratio and working capital turnover. The use of working capital in increasing the annual report profit from PT. Handjaya Mandala Sampoerna Tbk which is listed on the Indonesia Stock Exchange for the period 2015 to 2017.The results of this study indicate that the use of working capital from 2015 to 2017 has increased each year. Report on the source and use of working capital of PT. Handjaya Mandala Sampoerna Tbk has a good source of working capital because in 2015 to 2017 the source of working capital was greater than the use of working capital. The role of the use of working capital in increasing profits shows the level of effectiveness and efficiency in maintaining the company's financial turnover can run well. Analysis of the evaluation of the adequacy of working capital, the level of changes in liquidity. Total assets showed 2,926, current ratio showed 3,616 and working capital turnover showed 2,837. Keywords: Source, Use, Working Capital Adequacy Evaluation ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana penilaian Analisis Penggunaan Modal Kerja Dalam Meningkatkan Laba Pada PT. Handjaya Mandala Sampoerna Tbk Yang Terdaftar Di Bursa Efek Indonesia. Metode analisis yang digunakan adalah metode analisis deskriptif dan komparatif dengan menggunakan rasio kecukupan modal kerja yang terdiri dari tiga rasio yaitu  rasio total assets trun  rasio lancar  dan perputaran modal kerja . Penggunaan modal kerja dalam meningkatkan laba laporan tahunan dari PT. Handjaya Mandala Sampoerna Tbk yang terdaftar di Bursa Efek Indonesia periode 2015 s/d 2017.Hasil penelitian  ini menunjukkan bahwa penggunaan modal kerja tahun 2015 s/d 2017 setiap tahunnya mengalami peningkatan. Laporan sumber dan penggunaan modal kerja PT. Handjaya Mandala Sampoerna Tbk memiliki sumber modal kerja yang baik karena ditahun 2015 s/d 2017 sumber modal kerjanya lebih besar dari pada penggunaan modal kerja. Peran penggunaan modal kerja dalam meningkatkan laba menunjukkan tingkat efektivitas dan efesien terjaga perputaran keuangan perusahan dapat berjalan dengan baik. Analisis evaluasi kecukupan modal kerja tingkat perubahan likuiditas. Total assets menunjukkan 2.926, rasio lancar menunjukkan 3.616 dan perputaran  modal kerja menunjukkan 2.837. Kata Kunci : Sumber, Penggunaan , Evaluasi Kecukupan Modal Kerja.